A cohort analysis of wages in Indonesia - Skoufias, Emmanuel; Suryahadi, A. (Informa UK Limited, 2002)
This article uses repeated cross-sectional data for the years 1986 to 1998 to examine how the median and spread in the distribution of wages among workers of different age and gender were affected by the economic growth and contraction in output during this period. It finds that it is mainly the younger cohorts of male and female workers that have reaped the benefits of the growing employment and wages in the formal sector. The growing wage sector has been absorbing many of the young entrants into the labour market but more male workers than female workers. The increases in the median wages of these younger cohorts have been accompanied by a rise in the inequality of earnings. The level as well as the increase in dispersion is also higher for females of younger cohorts than male cohorts. The declines in real wages since the 1997 crisis have been relatively evenly distributed among male and female workers and across different age cohorts, while the impact of the crisis on wage inequality has been mixed.